PENGARUH PENGUNGKAPAN LAPORAN KEBERLANJUTAN, DAN PENGUNGKAPAN MANAJEMEN RISIKO TERHADAP NILAI PERUSAHAAN DENGAN RASIO LIKUIDITAS SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERBANKAN INDONESIA - Navelya Hadi; Herman Ruslim (Fakultas Ekonomi Universitas Tarumanagara, 2025)
This study aims to determine the effect of disclosure of sustainability reports (SR) and risk management (MR) on firm value (Tobin's Q) with the liquidity ratio (LCR ratio) as a moderating variable. Firm value in this study is the investor's perception of the level of success of a company which is reflected in the stock price. The research period is from 2018 – 2021 with a total of 164 samples consisting of 41 banking companies. The results of this study indicate that SR and MR have no significant effect on Tobin's Q, and the liquidity ratio is unable to moderate the relationship between disclosure of sustainability reports and risk management on firm value. These results show that the disclosure of sustainability reports and risk management does not significantly affect investors' decisions.